Penerapan Model Kooperatif Tipe STAD Dalam Pembelajaran Tematik Terpadu Di Sekolah Dasar (Studi Literatur) - Aulia Alfirzan (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine how to apply the STAD type cooperative model in integrated thematic learning in elementary schools. The research method used is a literature study (Library Research). The data used in this research is secondary data. Secondary data is data obtained not from direct observation. However, these data are obtained from the results of research that has been conducted by previous researchers. How to browse articles contained in online journals, thesis or dissertation results in the repository using Google Scholar. From the 11 articles above, it can be concluded that the application of the STAD type cooperative model can improve student learning outcomes, student activities, and teacher activities in the learning process.